Protein prescription and delivery practices in critically ill adults: A survey of Australian and New Zealand intensive care dietitians. Issue 5 (September 2022) - Lyons, G.C.E.; Summers, M.J.; Schultz, T.J.; Lambell, K.; Ridley, E.J.; Fetterplace, K.; Yandell, R.; Chapple, L.S.
Abstract: Background: Protein provision is thought to be integral to attenuating muscle wasting in critical illness, yet patients receive half of that prescribed. As international guidelines lack definitive evidence to support recommendations, understanding clinicians' views relating to protein practices is of importance. Objectives: The objective of this study was to describe Australia and New Zealand intensive care unit (ICU) dietitians' protein prescription and perceived delivery practices in critically ill adults, including common barriers and associations between ICU clinical experience and protein prescriptions for different clinical conditions. Methods: A 42-item descriptive quantitative survey of Australian and New Zealand intensive care dietitians was disseminated through nutrition and ICU society e-mailing lists. Data were collected on respondent demographics and reported protein practices including questions related to a multitrauma case study. Data were analysed using descriptive and content analysis and reported as n (%). Fisher's exact tests were used to compare experience and protein prescriptions. Results: Of the 67 responses received (one excluded due to >50% missing data), more than 80% of respondents stated they would prescribe 1.2–1.5 g protein/kg bodyweight/day for most critically ill patients, most commonly using European Society of Clinical Nutrition and Metabolism (ESPEN) guidelines to support prescriptions (n = 61/66, 92%). Most respondents (n = 49/66, 74%) thought their practice achieved 61–80% of protein prescriptions, with frequently reported barriers including fasting periods (n = 59/66, 89%), avoiding energy overfeeding (n = 50/66, 76%), and gastrointestinal intolerance (n = 47/66, 71%). No associations between years of ICU experience and protein prescriptions for 14 of the 15 predefined clinical conditions were present. Conclusions: Australian and New Zealand ICU dietitians use international guidelines to inform protein prescriptions of 1.2–1.5 g/kg/day for most clinical conditions, and protein prescriptions do not appear to be influenced by years of ICU experience. Key perceived barriers to protein delivery including avoidance of energy overfeeding and gastrointestinal intolerance could be explored to improve protein adequacy.